Cyanobacterial lipopeptides puwainaphycins and minutissamides induce disruptive and pro-inflammatory processes in Caco-2 human intestinal barrier model - Vašíček, Ondřej; Hájek, Jan; Bláhová, Lucie; Hrouzek, Pavel; Babica, Pavel; Kubala, Lukáš; Šindlerová, Lenka (Harmful algae, 2020)
Puwainaphycins (PUW) and minutissamides (MIN) are cyanobacterial lipopeptides found in various cyanobacterial species. The first possible target of human exposure to them is intestinal epithelium but effect of PUW/MIN on enterocytes is not known at all. Using differentiated Caco-2 cells, PUW F was found to be cytotoxic from 5 µM concentration based on lactate dehydrogenase release assay and total protein concentration. However, it is also able to induce production of interleukin 8 in non-cytotoxic concentrations 1 and 2.5 µM detected by ELISA. Effects of MIN A and C were similar but less pronounced compared to PUW F. On the other hand, MIN D was the least toxic compound with no significant pro-inflammatory effects. Surprisingly, pro-inflammatory activation of the cells by PUW F and MIN C resulted in an increase in tight junction (TJ) protein claudin 4 expression determined by western blot analysis and confirmed by confocal microscopy. Furthermore, decrease in expression of zonula occludens 3, another TJ protein, was observed after the exposure to PUW F. Taken together, these cytotoxic lipopeptides, especially PUW F, are to be studied more deeply due to their capability to activate and/or deregulate human enterocytes in low concentrations.
Keywords: Cyanobacteria; Intestinal Mucosa; Lipopeptides; Caco-2 buňky; lipopeptidy; lidé; sinice; Caco-2 Cells; těsný spoj; Tight Junctions; střevní sliznice; Humans